2023
DOI: 10.3389/fcvm.2023.978394
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility study of temporary permanent pacemaker in patients with conduction block after TAVR

Abstract: BackgroundLimited data exist on the use of temporary permanent pacemaker (TPPM) to reduce unnecessary PPM in patients with high-degree atrioventricular block (HAVB) after transcatheter aortic valve replacement (TAVR).ObjectivesThis study aims to determine the feasibility of TPPM in patients with HAVB after TAVR to provide prolonged pacing as a bridge.Materials and methodsOne hundred and eleven consecutive patients undergoing TAVR were screened from August 2021 to June 2022. Patients with HAVB eligible for PPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In a pilot study by our group, which included fewer cases, we showed that TPPM use is a reliable and safe method for patients with conduction disturbances after TAVR. 13 However, no study has evaluated the rates of PPM implantation using TPPM in different patient populations and no existing data has compared the rates of PPM implantation achieved with TPPM to those following current expert consensus. To the best of our knowledge, this is the first study to systematically evaluate the clinical outcomes of TPPM implantation in a multi-centre prospective population.…”
Section: Discussionmentioning
confidence: 99%
“…In a pilot study by our group, which included fewer cases, we showed that TPPM use is a reliable and safe method for patients with conduction disturbances after TAVR. 13 However, no study has evaluated the rates of PPM implantation using TPPM in different patient populations and no existing data has compared the rates of PPM implantation achieved with TPPM to those following current expert consensus. To the best of our knowledge, this is the first study to systematically evaluate the clinical outcomes of TPPM implantation in a multi-centre prospective population.…”
Section: Discussionmentioning
confidence: 99%
“…Another point is related to patients at risk without a clear indication for PPM implantation could benefit from temporary pacing. This has been evaluated and the current evidence [ 38 ] suggests that this approach is reasonable in this population, although this population should be better defined as we bridge the gap on who should/not receive a PPM. The transient pacemaker inserted during TAVR can also be used for atrial pacing with high negative predictive value to rule out HAVB in that moment.…”
Section: Management Of Conduction System Disease After Tavrmentioning
confidence: 99%